Development of a computer program for general use in the design of solar powered water pumping systems - Denny, Ernest Edward (My University, 2007)
Water is one of the basic necessities of life. In addition to being essential for the maintenance of life, this basic resource is a crucial requirement for combating poverty, hunger and disease in South African communities. In excess of twenty-nine percent of South African households do not have water in either their dwellings, or on site (source: 2005 RSA census data). This study documents an engineering solution to the problem of water pumping, utilising renewable energy (solar power) and readily available pumping hardware, configured via a structured design process. Resultant from the research, a software application has been developed that facilitates the design of solar (photovoltaic) powered water pumping applications. The selected design configuration of a nontracking, stand-alone, directly coupled system provides for the most robust and least complex design possible, making it imminently suitable for application in rural African conditions. Operation of the program is via a simple graphical user interface, with full and context sensitive help provided. It is tailored for use in Southern Africa and is provided with comprehensive databases of location dependant design information such as solar radiation, meteorology and magnetic declination data, together with expandable databases of pre-configured pump and solar panel hardware specification data. The program is manufacturer and component independent, with no affiliations in the choice of hardware. Design methodologies, together with a component matching strategy. Optimisation is achieved by a quantitative and efficiency 'best fit' analysis of the selected hardware components within the design context. Design output predictions are tabulated and graphed by month for a period of one year, allowing design visualisation. The application has been named 'South African Stand-alone Solar (PV) Water Pumping Design Aid', abbreviated as 'SAS-SWP' in its run-time form. The SASSWP application is illustrated in the functional overview provided in Figure 1.
M. Tech. (Electrical Engineering, Faculty of Engineering) Vaal University of Technology)
Keywords: Water pump aid; Solar water pump; 621.69; Solar energy; Pumping machinery